Informing practice in mathematics through the use of Herrmann’s Whole Brain® theory - E Randewijk; PH du Toit; AF Harding (South African Journal of Education)
In this research I explored how mathematics teachers can inform their teaching practice through a meta-reflective inquiry into methods of facilitating Whole Brain® learning in mathematics. Herrmann’s Whole Brain® theory was used as a lens through which to explore leading theories in the fields of constructivism, mathematics education and cognitive psychology by means of a participatory action research innovation, stretching over approximately 3 years. An analysis of these theories validated Herrmann’s Whole Brain® theory as the foundation for a synthesised integrated theory of practice, which also formed the epicentre of the conceptual framework for the research. The conceptual framework was also at the core of the participatory action research. The Herrmann Brain Dominance Instrument® (HBDI®) was administered to 8 teacher participants in a school mathematics department. Learners of each of the teacher participants also completed a questionnaire on how they perceived their teachers to facilitate learning and assessment of mathematics. These results were compared to the teacher participants’ Herrmann’s Brain Dominance Instrument®. Findings indicate that the Herrmann Brain Dominance Instrument® initiated scholarly reflection with teacher participants involved in facilitating and assessing the learning of mathematics. The collective reflexive practice was both part of the action research process and an outcome of the research itself. Findings also indicate that the thinking preferences of teacher participants, as tested by the Herrmann Brain Dominance Instrument®, are not necessarily indicative of their teaching style and teachers involved in post-graduate studies indicated an ability to access their non-dominant thinking mode situationally.